An Analytical Study of Modupeola Fadugba’s Paintings - Alawode, Musa Ajibola; Aliyu, Muhammed (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
Modern Nigerian art emerged through formal and informal training: formal art training includes the artistic knowledge acquired within the four walls of classrooms. Informal art training, on the other hand includes apprenticeship and self-taught systems. Self-taught artists have no known masters, but are naturally talented. The paper focuses on Modupeola Fadugba, a female self-taught painter. It adopted qualitative research design, using historical and descriptive approaches to discuss Fadugba’s paintings with particular emphasis on her background, style, theme and media. It was discovered that Fadugba is a realistic painter whose major theme is agitation. Through her works, she agitated for better condition for Nigerian women who have always been at the receiving end of cultural, political and social impediment in the country.